2019
DOI: 10.1111/1365-2656.12975
|View full text |Cite
|
Sign up to set email alerts
|

Does divergent selection predict the evolution of mate preference and reproductive isolation in the tropical butterfly genus Melinaea (Nymphalidae: Ithomiini)?

Abstract: Many studies have shown that speciation can be facilitated when a trait under divergent selection also causes assortative mating. In Müllerian mimetic butterflies, a change in wing colour pattern can cause reproductive isolation. However, colour pattern divergence does not always lead to reproductive isolation. Understanding how divergent selection affects speciation requires identifying the mechanisms that promote mate preference and/or choosiness. This study addresses whether shifts in wing colour pattern dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…We found a strong dampening of local speciation in the Central (Hill et al, 2012;Jiggins et al, 2006;McClure & Elias, 2016McClure et al 2019). Contrasting with those clades, four other Amazonian radiations showed diversification rates decreasing through time, meaning that diversification was highest immediately after the retreat of the Pebas.…”
Section: Diversification Across the Whole Neotropics After The Demimentioning
confidence: 60%
See 2 more Smart Citations
“…We found a strong dampening of local speciation in the Central (Hill et al, 2012;Jiggins et al, 2006;McClure & Elias, 2016McClure et al 2019). Contrasting with those clades, four other Amazonian radiations showed diversification rates decreasing through time, meaning that diversification was highest immediately after the retreat of the Pebas.…”
Section: Diversification Across the Whole Neotropics After The Demimentioning
confidence: 60%
“…Drivers of diversification in the core group probably include radiation on Solanaceae (Willmott & Freitas, ), which were already diverse in the Neotropics during the Miocene (Dupin et al, ), in conjunction with a diversity of habitats along the slopes of the Andes. Speciation was also potentially mediated by shifts in mimicry patterns (Chazot et al, ; Willmott & Mallet, ), which can generate reproductive isolation in mimetic butterflies (Jiggins, Naisbit, Coe, & Mallet, ), including Ithomiini (Jiggins et al, ; McClure et al ). Those ecological drivers of diversification were probably at play both in the Andes and in non‐Andean areas, after the Pebas retreat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the geographic overlap in distribution, a recent genetic study showed limited gene flow [4]. Reproductive isolation in mimetic butterflies can be driven by multiple factors, notably non-random mating based on color pattern and/or sexual pheromones [6][7][8]. Determining whether the closely related subspecies of I. salapia differ in the chemical composition of volatiles is, therefore, of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Wing colour pattern is known to cause pre‐ and post‐zygotic reproductive isolation in Müllerian mimetic butterflies (e.g., Chamberlain, Hill, Kapan, Gilbert, & Kronforst, 2009; Jiggins et al, 2001; Mallet & Barton, 1989; Merrill et al, 2011; Merrill et al, 2012; Naisbit, Jiggins, Linares, Salazar, & Mallet, 2002), including Ithomiini (McClure et al, 2019).…”
Section: Discussionmentioning
confidence: 99%